The Primary Immunodeficiency Database in Japan - Mitsui-Sekinaka, Kanako; Sekinaka, Yujin; Endo, Akifumi; Imai, Kohsuke; Nonoyama, Shigeaki (Frontiers in Immunology, 2022)
The Primary Immunodeficiency Database in Japan (PIDJ) is a registry of primary immunodeficiency diseases (PIDs) that was established in 2007. The database is a joint research project with research groups associated with the Ministry of Health, Labor and Welfare; the RIKEN Research Center for Allergy and Immunology (RCAI); and the Kazusa DNA Research Institute (KDRI). The PIDJ contains patient details, including the age, sex, clinical and laboratory findings, types of infections, genetic analysis results, and treatments administered. In addition, web-based case consultation is also provided. The PIDJ serves as a database for patients with PIDs and as a patient consultation service connecting general physicians with PID specialists and specialized hospitals. Thus, the database contributes to investigations related to disease pathogenesis and the early diagnosis and treatment of patients with PIDs. In the 9 years since the launch of PIDJ, 4481 patients have been enrolled, of whom 64% have been subjected to genetic analysis. In 2017, the Japanese Society for Immunodeficiency and Autoinflammatory Diseases (JSIAD) was established to advance the diagnosis, treatment, and research in the field of PIDs and autoinflammatory diseases (AIDs). JSIAD promotes the analysis of the pathogenesis of PIDs and AIDs, enabling improved patient care and networking via the expansion of the database and construction of a biobank obtained from the PIDJ. The PIDJ was upgraded to “PIDJ ver.2” in 2019 by JSIAD. Currently, PIDJ ver.2 is used as a platform for epidemiological studies, genetic analysis, and pathogenesis evaluation for PIDs and AIDs.